Fi fi brindacier - Lindgren, Astrid; Maja, Daniel (Vanves : Hachette Jeunesse, 1945)
Escapades of a lucky little girl who lives with a horse and a monkey--but without any parents--at the edge of a Swedish village.
Keywords: Pippi Longstocking -- Fiction